PERFORMANCE EVALUATION AND EMISSION ANALYSIS OF VARIABLE COMPRESSION RATIO DIRECT INJECTION DIESEL ENGINE - Kumar, Narender; Soni, Shyam; Sharma, Dilip; Srivastava, Anmesh (MATTER: International Journal of Science and Technology, 2016)
With the advent of enhancing environmental and fossil energy concerns, sustainability that can be done with the effective utilization of presently used energy sources, is of major concern. The world of today is working hard to solve energy related problems, such as, energy supply security, emission control, economy and conservation of energy etc. A great potential lies in the hand of automotive engineers and scientists to use these exhisting reserves of petrolium products effectively. In this present study, effect of compression ratio on the performance and emissions of the diesel engine at various loads is done. While conducting the experiment compresssion ratio range is kept from 18 to 22. It is observed that compression ratio 21 is giving maximum Brake thermal efficiency at part as well as full load. Brake specific fuel consumption and Brake specific energy consumption is found minimum at compression ratio 21.